(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Objectives:To evaluate and compare the effectiveness of metformin plus pioglitazone versus metformin alone in treatment of raised alanine aminotransferase (ALT) in nonalcoholic fatty liver disease (NAFLD) in patients with newly detected diabetes mellitus (DM) and impaired glucose tolerance (IGT). Materials and methods: In this open label clinical trial, newly detected DM and IGT patients with raised ALT and ultrasound proven NAFLD were treated with either metformin and pioglitazone combination (group 1) or metformin alone (group 2). They were followed up upto 6 months. Results:Total number of patients was 49 (27 in group 1 and 22 in group 2) and there was male predominance in either group. Age was almost identical between two groups (46±9.3 and 45.4±5.7 years in group 1 and group 2 respectively). Significant reduction in values of fasting blood glucose (FBG), 2 hours post breakfast values (ABF), HbA1c, cholesterol (CHOL), triglycerides (TG) and ALT of the study subjects were achieved in either group after six months (Group 1: FBG 8.89±1.4 vs 6.37±0.5 mmol/l, ABF 13.2±2.07 vs 8.34±0.84 mmol/l, HbA1c 8.15±0.87 % vs6.7±0.40%, CHOL 205.26±30.74 vs 178.89±18.59 mg/dl, TG 226.15±50.06 vs 155.85±20.99 mg/dl, ALT 91.52±23.14 vs 45.74±12.63 mg/dl and in Group 2 : FBG 9.39±2.26 vs 6.98±1.20 mmol/l, ABF 13.38±2.93 vs 9.13±1.46 mmol/l, HbA1c 8.10±0.92 % vs7.03±0.71%, CHOL 206.55±29.9 vs 195±23.55 mg/dl, TG 235.59±46.22 vs 178.91±38.24 mg/ dl, ALT 105.59±18.63 vs 66.36±16.02 mg/dl).In comparison between two groups, Group 1 had better metabolic control compared to their counterpart of Group 2 at the end of 6 months [Group 1 vs Group 2: FBG (p=0.024), ABF (p=0.022), CHOL (p = 0.010), TG (p =0.010)]. There was significant reduction in ALT as well (p = 0.000). Conclusion:Combination of metformin and pioglitazone is more effective than metformin alone in reducing ALT in NAFLD in newly detected DM and IGT patients. J Bangladesh Coll Phys Surg 2014; 32: 194-199